70 let profesorice Božene Tokarz, dopisne članice Slovenske akademije znanosti in umetnosti - Jesenšek, Marko (Slavia Centralis, 2020)
The author of the article gave kind words to Božena Tokarz, a corresponding member of SAZU, on her 70th birthday.
Keywords: biography; linguistics; scientist; researcher; Božena Tokarz